Stress, Nutritional Status and Blood Glucose Levels among Patients with Diabetes Mellitus Type 2 - Dyah Ayu Kusuma Wardani; Sugiarto Sugiarto; Risya Cilmiaty (Intelektual Pustaka Media Utama, 2018)
Prevalence of diabetes mellitus (DM) was increased significantly. Stress increased cortisol could increase blood glucose levels while obesity could increase insulin resistance. Objective of this study was to examine correlation of stress and nutritional status with blood glucose levels in patients with DM type 2. Design study was cross sectional using 120 samples from patients with DM type 2 at Polyclinic of Internal Disease Dr. Moewardi Hospital Surakarta during April-May 2018. Variables in this study were stress with perceived stress scale 10 items (PSS-10), nutritional status with body mass index (BMI) and blood glucose levels with fasting blood glucose (FBG) and post-prandial blood glucose (PPBG) examination. The results showed that mean of FBG was 152.9±63.66 mg/dL and PPBG was 213.96±70.17 mg/dL. There was no significant correlation between stress and blood glucose levels, by FBG (p=0.389) and PPBG (p=0.202). However, there was significant correlation between nutritional status and PPBG (p=0.016), but FBG was not significant (p=0.209). In conclusion, there was significant correlation between nutritional status and PPBG in patients with DM type 2, but FBG was not significant. However, there was no significant correlation between stress and blood glucose levels in patients with DM type 2.